Project OPTIMIZE (Observing Practical & Transformed Innovative Mentorship to Ignite Zeal Excellence): A Gauge to Determine Expected Outcomes Among Science Teachers in Luis Aguado National High School - TOBILLA, JOAN; Varias, Leoniza D (SEAMEO SEAMOLEC, 2024)
The study is highly deemed to measure the effectiveness of Project OPTIMIZE (Observing Practical & Transformed Innovative Mentorship to Ignite Zeal Excellence) to achieve the expected outcomes among science teachers in Luis Aguado National High School. Specifically, it is desired to determine to what extent do science teachers progress toward excellence as they participate on the said project. It has been qualitative research. The study was conducted at Luis Aguado National High School in Trece Martires City, Cavite, Philippines. The study participants were 9 teachers in the Science Department. They were map out according to their profile, number of years in teaching, specialization, special skills and interests. Moreover, a standard tool to determine and monitor teacher’s progress in terms of checking of daily lesson logs, class observations and submission of pertinent school reports. Being a qualitative study, provision of technical assistance is shown throughout the period. Coaching and mentoring is congruent on the priority needs of the teacher. The teacher’s progress monitoring report is tremendously significant on the monitoring and checking of teacher’s outputs. In addition, Learning Action Cells and Focus Group Discussion were conducted every quarter to develop the optimum potentials of science teachers. As part of the evaluation of the teacher, document analysis is done in every activity. The present study has significantly impacted the following (1) 9 out of 9 science teachers provide technical assistance to equipped their competencies and performance in teaching and learning delivery; (2) address the priority needs through conducting consultation via coaching and mentoring, focus group discussion, fostering collegial collaboration via benchmarking of best practices, document analysis and related goals and (3) recognize the achieved goals and targets as well as intensify their strength and potentials. Relatively, this project offered a systematic process to quality assure outputs, innovations via work smart and provide technical assistance on the identified needs, findings, and observations. Furthermore, giving optimize possibilities to excellence hence as learning opportunities among science teachers to be the best version of themselves leading into ways forward to transform highly competent and versatile teachers of the 21st century learners.